2018
DOI: 10.1016/j.aos.2017.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Professional repositioning during times of institutional change: The case of tax practitioners and changing moral boundaries

Abstract: If citing, it is advised that you check and use the publisher's definitive version for pagination, volume/issue, and date of publication details. And where the final published version is provided on the Research Portal, if citing you are again advised to check the publisher's website for any subsequent corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
71
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 44 publications
0
71
0
1
Order By: Relevance
“…SS analysts have therefore been struggling to reposition themselves in the field of investment advice, eclipsing their previous functions as suppliers and distributors of essential information by performing a more contingent role of trusted consigliere-advisors who have access to privileged information and use it to co-construct interpretative knowledge along with actors on the BS. Previous research has shown how financial professionals can successfully employ social skill in order to transform existential threats into opportunities (Radcliffe et al 2018). However, given the nature of changes in the field of investment advice that have disrupted established positions in recent years, the consigliere role coveted by SS analysts has effectively been a mitigation strategy that has provided economic and interorganizational justification, perhaps temporarily, for the continued existence of SS analysts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SS analysts have therefore been struggling to reposition themselves in the field of investment advice, eclipsing their previous functions as suppliers and distributors of essential information by performing a more contingent role of trusted consigliere-advisors who have access to privileged information and use it to co-construct interpretative knowledge along with actors on the BS. Previous research has shown how financial professionals can successfully employ social skill in order to transform existential threats into opportunities (Radcliffe et al 2018). However, given the nature of changes in the field of investment advice that have disrupted established positions in recent years, the consigliere role coveted by SS analysts has effectively been a mitigation strategy that has provided economic and interorganizational justification, perhaps temporarily, for the continued existence of SS analysts.…”
Section: Discussionmentioning
confidence: 99%
“…These findings challenge existing notions in the literature about the informational value of analyst reports in investment decision making and shed new light on sources of analysts' value in the field of investment advice as well as the development and use of reports as relational devices. Finally, we show that professionals employing social skill (Fligstein 2013) do not always succeed in advancing their professional projects (Radcliffe et al 2018;Suddaby and Viale 2011) but can be restricted to strategies of mitigation instead.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In doing so, they inevitably update their habitus and also, because they occupy a social position within the field, shape the nuances of how a field values particular capitals. For example, reputational risk awareness becomes more valued than pure compliance in current tax knowledge (Radcliffe, Spence, Stein, & Wilkinson, 2018), so updating both cultural capital and, given their entanglement, the combination of capitals valued by the field. These recursive dynamics elaborate on Cardinale's framework, by showing how capitals orient the pre-reflexive everyday work of corporate executives, that in turn reinforces the institutionalization of tax strategies that lie within a certain band of the tax minimization spectrum.…”
Section: Empirical Illustration: Switching Between Fieldsmentioning
confidence: 99%
“…Chandler (2017, 190) reminds us that while some issues of professional etiquette and ethical conduct endure (such as 'low balling'), others, such as advertising, once perceived as a serious offence, are now deemed acceptable: 'while some components of the model of the ethical accountant remain immutable and the problems of clarifying appropriate behaviour insoluble, other issues disappear as society evolves and notions of ethics change'. Studies in more modern-day settings also point to the way in which shifting moral boundaries in wider society result in the renegotiation of moral imperatives by professionals (Radcliffe et al 2018). This phenomenon is deemed much more discernible at the level of individual actors.…”
Section: Introductionmentioning
confidence: 99%